The role of bowel for minimally invasive treatment of stricture disease - Kronstedt, Shane; Kaldany, Alain; Patel, Hiren V.; Elsamra, Sammy E. (Frontiers in Urology, 2023)
The management of urinary tract stricture disease has evolved over the last several decades, with robotic surgery representing a bourgeoning method for urologic reconstruction. Conventionally, proximal and mid-ureteral strictures, as well as lengthy urethral strictures, have presented a challenge for surgeons to create tension-free repairs. Options for repair include endoscopic dilation, endopyelotomy, ureteroplasty or pyeloplasty, and urethroplasty. Small and large bowel can be incorporated into various urinary tract stricture repairs. Their use has proven successful in reconstructing both upper and lower urinary tract strictures and offers flexibility for complex cases such as lengthy or multifocal strictures. While the use of bowel, most notably the appendix, for stricture repair is not a novel concept, a growing body of evidence supports its use with minimally invasive robotic approaches. In addition, there has been a substantial amount of recent data suggesting low rates of postoperative complications and long progression-free survival after robotic stricture repair using small bowel or rectum. We present a comprehensive review of literature outlining the role of the small bowel, appendix, and rectum in the minimally invasive repair of urinary tract stricture disease, as well as a description of the various techniques employed.